Review of Thomas MacGreevy and the Rise of the Irish Avant-Garde, by Francis Hutton-Williams - Hélène Lecossois (Review of Irish Studies in Europe)
Review of Thomas MacGreevy and the Rise of the Irish Avant-Garde, by Francis Hutton-Williams (Cork: Cork University Press, 2019). 148pp, ISBN: 978-1-78205-356-9. €40.10 (hardback).